Management of Congenital Nasolacrimal Duct Obstruction with Probing, Experience in a Mexican Eye Center - Zuazo, Francisca; Morales, Osiris Olvera; Canales, José L. Tovilla; Castañeda, Ángel Nava (Nepalese Journal of Ophthalmology, 2019)
Objective: To describe the management, complications and prognosis of lacrimalprobing in patients with congenital nasolacrimal duct obstruction (CNLDO). Materials and Methods: Retrospective, observational and analytical study. We studied the prevalence, symptoms and signs, both before and after probing, in patients with CNLDO diagnosed between 2010 and 2017 at Instituto Fundación Conde deValenciana. Results: The prevalence at our hospital of congenital nasolacrimal duct obstruction in children less than 1 year of age was 16.1%. 71 eyes of 56 patients undergoing probing were analyzed. 61% of patients were male. The right eye was affected in 46.4%.The average age of diagnosis of CNLDO was 10.2±7.6 months. 84.5% consulted for excessive tearing and 73.2% because of eye discharge. On ophthalmological examination, 71.8% had increased tear meniscus and 45.1% had discharge from punctum when digital pressure was applied to the lacrimal sac. The average age at the time of probing was 14.1±8.4 months. Subsequent to the probing, only 21.1% reported presence of tearing and 5.6% reported ocular discharge, both with a statistically significant reduction (p<0.05 from pre-op). After probing, only 16.9% of eyes had increased tear meniscus and 11.3% presented discharge from punctum after pressure at the lacrimal sac. Both decreases were statistically significant (p<0.05). 2 eyes (2.82%)of 2 patients required a second probing to obtain full resolution. Conclusion: Probing was successful in 76.1% of eyes. Success was observed even inpatients over 2 years of age. There was a statistically significant decrease of both signs and symptoms of CNLDO with lacrimal probing.